Speech Act in Si Tenggang Anak Derhaka Saga By A. Samad Ahmad - Fella Kaulika; Rozanna Mulyani; Hariadi Susilo (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2022)
This study focuses on the form of Si Tenggang's speech as the main character in the Hikayat Si Tenggang Anak Derhaka. The data in this study were examined using Searle's (1980) illocutionary speech act theory. This study applies a qualitative descriptive research design with a listening method and note-taking technique for data collection. Meanwhile, the matching method with certain element sorting techniques was used to analyze the data. After the data was analyzed with a total of 103 data, it can be concluded that all forms of speech proposed by Searle (1980) regarding the form of speech acts are found in the speech of Si Tenggang Anak Derhaka with the number of each form starting from the most to the least as follows: Representative presented in 56 utterances, Expressive has a total of 19 utterances, Directive has a total of 15 utterances, Commissive has a total of 11 utterances, and Declarative is presented in 2 utterances. There are 34 meanings that Si Tenggang wants to convey to his interlocutor in this saga, namely: concluding, confirming, assuming, confirming, asking for confirmation, stating presuppositions, describing, asking for clarification, expressing joy, expressing anger, expressing annoyance, expressing joy, expressing disagreement, yelling, complaining, thanking, expressing anxiety, expressing desire, calming the other person, expressing hope, expressing regret, calling, inviting, ordering, ordering, planning something, threatening, refusing, promising, apologizing, swearing, declaring power had been given to him and declared his voyage plans.